Preparation and diagnosis of heterocyclic tetra and pentecyclic compounds derived from amine compounds - Ahmed mustafa sultan Ali; Noora Najeh Abdel Sada Hassan; Manal Younis Ibrahim Elias; Saba Thamer Jaleel Ahmed; FATIMAH SHAHEED GHAZI ZAHIR (Genius Journals, 2024)
Schiff bases are nitrogen analogues to carbonyl compounds, but they differ from them in chemical activity, molecular structure, and stereoscopic formulas. Since the carbonyl group has a flat three-chamber structure, the bond angle between the oxygen atom, the carbonyl carbon atom, and the carbon atom of the groups attached to it is equal to 120, and the carbonyl group is polarized, as the carbon atom carries a partial positive charge and the oxygen atom a partial negative charge, which makes this group suitable for adding reagents. Searching for the nucleus (Nucleophilic Addition) from the top and bottom of the carbon atom and the Addition searching for electrons (Electrophilic Addition).
Keywords: heterocyclic; nitrogen analogues; molecular structure